Descartes and his critics on passions and animals. Issue 5 (3rd September 2022) - Thomas, Evan
ABSTRACT: Descartes' theory of the passions has important connections to his view that nonhuman animals are automata. In this paper, I show how critics of animal automatism exploited these connections. I interpret a criticism of animal automatism developed by Gabriel Daniel (1649–1728). Daniel argues that animal automatism commits Descartes to an implausible account of the phenomenology of conflicts between passion and reason. If animal bodies act by mere automatic mechanism, then when a human being resists their animal impulses they should experience a conflict between the disposition of their body and their rational soul. However, our experience of conflicts between passion and reason instead suggests that these conflicts are internal to the soul. Daniel's objection to Cartesian animal automatism was later criticized by David Renaud Boullier (1699–1759), but Boullier himself raises an objection to Cartesian animal automatism that develops insights from Daniel. I argue that Boullier succeeds in raising a powerful objection to Cartesian animal automatism.